The Influence of Leadership and Work Communication on Organizational Citizenship Behavior - Melawati Dewi; Edy Hartono; Sandi Nasrudin Wibowo (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2022)
This study aims to determine the effect of leadership and work communication partially or simultaneously on OCB. The sampling technique is random sampling. The population in this study was 191 and the sample taken was 66 respondents. The results of this study indicate that leadership has a significant effect on OCB seen from > that is 10,805 > 1,669 and the value (sig) 0.000 <0.05, work communication has a positive and significant effect on OCB seen also from > that is 10,817 > 1,669 and the value (sig) 0.000 <0.05 and the variables of leadership and work communication (simultaneous) have a positive and significant effect on OCB which is indicated by Fcount>Ftable, namely 101.208>3.14 and the value (sig) 0.000<0.05.